Implementation of the Zoning Policy for New Student Admissions From a Legal Sociology Perspective - Dwiyanto Budi Santoso (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
In order to fulfill the educational rights of every citizen which have been regulated in law, one of which is to realize services and equal distribution of educational quality, the Government issued regulations regarding the zoning system. The policy regarding the zoning system is stated in Minister of Education and Culture Regulation Number 14 of 2018, namely Admission of New Students (PPDB) which emphasizes the distance or radius between the student's house and the school, so whoever is closer to the school is more entitled to receive educational services from that school. Since it was implemented in 2018, the New Student Admissions (PPDB) zoning system has reaped sharp pros and cons and problems in society. The aim of this research is to analyze the pros and cons phenomena and problems of the zoning system in society within the framework of legal sociology as an evaluation of efforts to improve the system. This research uses a literature study method by collecting and analyzing results from various sources and relevant data. The results of this research reveal that the main challenges in implementing zoning policies are the lack of preparedness of stakeholders affected at the local level, the lack of distribution in public schools, school infrastructure, teacher resources, educational assistance, as well as a pragmatic culture or cheating that is commonly carried out. The implementation of the zoning system must always be evaluated and improved in order to achieve quality education.